2016
DOI: 10.15252/msb.20167144
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐specific correlation of RNA and protein levels in human cells and tissues

Abstract: An important issue for molecular biology is to establish whether transcript levels of a given gene can be used as proxies for the corresponding protein levels. Here, we have developed a targeted proteomics approach for a set of human non‐secreted proteins based on parallel reaction monitoring to measure, at steady‐state conditions, absolute protein copy numbers across human tissues and cell lines and compared these levels with the corresponding mRNA levels using transcriptomics. The study shows that the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
308
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(370 citation statements)
references
References 37 publications
32
308
2
4
Order By: Relevance
“…The correlation between the absolute mRNA and protein levels of different genes and across different tissue-types has been used to estimate the level at which the protein levels are regulated [20, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…The correlation between the absolute mRNA and protein levels of different genes and across different tissue-types has been used to estimate the level at which the protein levels are regulated [20, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…(Edfors et al., 2016). These authors reported a gene‐specific linear correlation between mRNA and protein levels across a wide range of tissues, including muscle, while we showed that changes in transcript levels are minor compared to those in protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…() and Edfors et al . () demonstrated that the predictability of protein copy numbers from RNA levels could be enhanced if a gene‐specific RNA‐to ‐ protein conversion factor, which was shown to be independent of the eukaryotic tissue cell type, was introduced. Furthermore, it has been demonstrated that a differential expression of a gene under different conditions is accompanied by a higher likelihood of a corresponding change in protein levels (Koussounadis et al ., ).…”
Section: Introductionmentioning
confidence: 99%